Correction to: “Sumatera Task Force – A Field Report of Final-Year Medical Student Deployment in Flash Flood Disaster Response” - Dian Andriani Ratna Dewi (The ASEAN Journal of Military and Preventive Medicine, 2026)
Correction Following publication of the above article, the Editorial Office received a post-publication concern regarding the accuracy and attribution of Reference 22. The journal initiated a post-publication editorial review. The authors were asked to clarify the reference in question, review the complete reference list, verify the relationship between individual citations and the claims they supported, and identify any additional inaccuracies requiring correction. The authors subsequently submitted a formal response, an itemised reference-verification report, and a revised manuscript. The Editorial Board also conducted an independent audit of the published references and citation–claim relationships. The review confirmed the concern regarding Reference 22 and identified additional bibliographic inaccuracies and citation–claim mismatches in the originally published article. The article has therefore been formally corrected.